6+(5x+13)=(7x-25)

Simple and best practice solution for 6+(5x+13)=(7x-25) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+(5x+13)=(7x-25) equation:



6+(5x+13)=(7x-25)
We move all terms to the left:
6+(5x+13)-((7x-25))=0
We get rid of parentheses
5x-((7x-25))+13+6=0
We calculate terms in parentheses: -((7x-25)), so:
(7x-25)
We get rid of parentheses
7x-25
Back to the equation:
-(7x-25)
We add all the numbers together, and all the variables
5x-(7x-25)+19=0
We get rid of parentheses
5x-7x+25+19=0
We add all the numbers together, and all the variables
-2x+44=0
We move all terms containing x to the left, all other terms to the right
-2x=-44
x=-44/-2
x=+22

See similar equations:

| 1/2+m=-3/4 | | 4x-5(2x+1)=0x-5 | | 4x-10=-8x+10 | | 140=m+64-4 | | x^2(x-6)=3x-4(2-x) | | -7=2u+3 | | 167=88-v | | -54+2x=18+4x | | 4​(y+3​)​=5​(y-4​) | | 6^t=33 | | 8a=a-7*15a. | | 6x^2+36X+5=0 | | 6x–11=3x+16 | | 4(4+4)+y=1 | | c/17+5=9 | | ∠A=8x-8∠B=5x+25 | | c17+5=9 | | −2y−3y+8=8−5y−12A | | 10q+11=11 | | t+14=2712 | | 36+7x=-20 | | -7.9=3/u-3.1 | | 15x+5/3=5x+6 | | t+10=80 | | 3(c+1)=15 | | 4x-20/2=2x-10 | | 2x+3(7+x)=31 | | 10y-1=11 | | 589+24.25m=1762 | | 8-4x/10=4+2x | | 200y-400+28-505+10-20y-203y=2115 | | (48+x)=(64) |

Equations solver categories